Italian Teachers' Well-Being Within the High School Context: Evidence From a Large Scale Survey - Barbieri, Barbara; Sulis, Isabella; Porcu, Mariano; Toland, Michael D. (Frontiers in Psychology, 2019)
This paper aims to investigate the relationship between Italian teachers’ well-being, socio-demographic characteristics and professional background. Using data from the 2015 wave of the Program for International Student Assessment (PISA) we considered information collected by the questionnaire completed by a total of 6,491 teachers in the sampled schools. Moving from existing literature on teachers’ well-being, we investigate several aspects related to the teachers’ working environment, career motivation and investment, and job satisfaction. We assess the variability in the observed outcomes attributable to school factors and heterogeneity between disciplines. Measurement models are combined in a multilevel setting in order to define teachers’ well-being on a broad perspective while accounting for the multiple sources of heterogeneity due to several factors (e.g., discipline, teacher professional background, and individual differences) occurring at different levels of the data structure. In general, results show that the teachers’ positive perception of the working environment in terms of availability of adequate human and physical resources, and professional development opportunities, provide a substantial state of well-being at work, and are related to teachers’ job satisfaction. Moreover, results highlight the key role of transformational leadership in defining a teacher’s well-being. Findings and implications are discussed.